Outcomes of antituberculosis treatments at 18 months follow-up in TB-HIV co-infected patients on ART: A retrospective review of 166 cases - Pongsak Chunpongthong (2018)
Objectives: To study the outcomes of antituberculosis treatment in HIV/AIDS patients on antiretroviral therapy (ART). Material and Method: This retrospective cohort study was performed by reviewing medical records of 166 patients co-infected with tuberculosis (TB) and HIV in a hospital in Thailand seen between January 2005 and February 2008. These patients were treated with both antituberculosis (antiTB) and antiretroviral drugs (ART) and were followed for 18 months after the beginning of antiTB. Results: Total 166 HIV patients with TB on ART and anti tuberculosis drugs were analyzed. The median age of patients was 36 years (20-72). Sixty-nine (41.6%) patients had pulmonary TB and 97 (58.4%) disseminated TB. Among them, 127 (76.5%) were cured and 15 (9.0%) had unsuccessful treatment. Median time for successful treatment was 10.8 months (6-32) during 18 months follow-up. There was no statistically significant difference in outcome of tuberculosis between the NVP and EFV base regimens in combination with rifampicin (5.4% vs. 10.8%, p = 0.751). Conclusion: Majority of HIV patients on ART with tuberculosis were successfully treated with antiTB drugs with median time of 10.8 months and no significant difference of adverse events reported between NVP and EFV.